Établissements d’Enseignement Superieur: Inclusion et de l’environnement de travail - Pereira, Carlos Eduardo Candido [UNESP]; Bizelli, José Luís [UNESP]; Leite, Lúcia Pereira [UNESP] (FapUNIFESP (SciELO), 2017)
People with disabilities enter the labor market to carry out productive activities and build their independence. The advance of legislation does not preclude difficulties in entering and remaining in labor organizations. In this investigation, the chosen field was a public university. Participants were technical and administrative staff and teachers with disabilities, who reported on their entry experience and working conditions that were offered at the institution. The analysis reveals the unpreparedness of the organization at the time of receiving the workers; the prejudice and discrimination in dealing with colleagues and managers; and indifference to the law. Despite the existing material conditions, servants show appreciation and motivation for having access to employment.
Organizações de ensino superior: Inclusão e ambiente de trabalho
Higher education organizations: Inclusion and work environment
Keywords: Higher Education; Inclusion; Labor market